A Comparative Analysis of Mobile Application Development Approaches: Mobile Application Development Approaches - Masaad Alsaid, Mohamed Abdal Mohsin; Ahmed, Tarig Mohamed; Jan, Sadeeq; Khan, Fazal Qudus; Mohammad; Khattak, Amjad Ullah (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Over the last decade, there has been a significant increase in the development of mobile applications. The performance of the developed applications depends largely on the development approaches. There are two widely used approaches: (1) native, where the application is targeted and developed for a specific platform, (2) crossplatform, where the developed application runs on multiple platforms. This paper aims to address the question of which approach should be used in various scenarios. We have performed a detailed comparison of the two approaches by developing a mobile app using both approaches. Experiments are performed using Android and iOS, the two most well-known mobile Operating System. The criteria of deciding the best approach include performance, usability and support. Our results show that both approaches are viable depending on the requirements and type of the application to be developed, with native having an edge. Guidelines are presented at the end to help the developers in choosing the best approach. The fundamental differences and advantages of each approach are discussed.